Draft Tenth Five Year Plan (2002-2007) and Annual Plan (2002-2003) Government of Mizoram - Planning Commission (Planning Commission, 2002)
Mizoram is bounded on the north by the States of Assam and Manipur, on the east and south by Chin Hills of Myanmar and on the west by Chittagong Hill Tracts of Bangladesh and the State of Tripura. It covers an area of 21,081 Sq.Km. The hill areas of Mizoram enjoy cool temperate climate. The average annual rainfall is 217.5 cm. The temperature varies between 12 and 18 degrees Celsius in winter and 18 and 29 degree Celsius in summer. For administrative purposes, Mizoram is divided into 8(eight) district namely, Aizawl District, Lunglei District, Kolasib District, Mamit District, Champhai. District, Serchhip District, Saiha District and Lawngtlai District. Each District is headed by a Deputy Commissioner while each Sub-Division is under the administrative control of Sub-Divisional Officer.
Planning & Programme Implementation Department, Government of Mizoram.